Establishing the Participatory Area-based Mechanisms for the Development of the Old Town in Surat Thani Municipality, Thailand to Improving the Quality of Economy, Society and Environment to the Smart City - Phongphanich, Nara; Phongphanich , Dolluck (Journal of Ecohumanism, 2025)
Surat Thani old town into a smart city through collaborative efforts across sectors, utilizing participatory action research and community action planning, leaders from various sectors were engaged. Qualitative and quantitative methods were employed, with data analyzed through content analysis and descriptive statistics. The study area included several key locations within Surat Thani Municipality. Results indicated the successful development of creative mechanisms for the town's preservation and transition to a smart city, achieved through sector-wide participation. Seven community researchers, representing different sectors, facilitated the process. Proposed guidelines and innovations were formulated to guide preservation and development efforts, emphasizing participatory planning and the integration of smart city concepts. The research outcomes informed policymaking, academic collaboration, and commercial ventures, contributing to Surat Thani’s vision as a livable smart city. The findings were utilized to create a master plan and strategic framework for short, medium, and long-term development goals. Collaboration among academic institutions and government agencies further enhanced the implementation of these plans. Commercially, public relations media were utilized to promote tourism and community development, fostering additional income opportunities within the community.